Balance Changes in Patients With Relapsing-Remitting Multiple Sclerosis: A Pilot Study Comparing the Dynamics of the Relapse and Remitting Phases - Findling, Oliver; Rust, Heiko; Yaldizli, Özgür; Timmermans, Dionne P. H.; Scheltinga, Alja; Allum, John H. J. (Frontiers in Neurology, 2018)
Aims: To compare balance changes over time during the relapse phase of relapsing-remitting multiple sclerosis (RRMS) with balance control during the remitting phase. Methods: Balance control during stance and gait tasks of 24 remitting-phase patients (mean age 43.7±10.5, 15 female, mean EDSS at baseline 2.45± 1.01) was examined every 3 months over 9 months and compared to that of 9 relapsing patients (age 42.0±12.7, all female, mean EDSS at relapse onset 3.11 ± 0.96) examined at relapse onset and 3 months later. Balance was also compared to that of 40 healthy controls (HCs) (age 39.7±12.6, 25 female). Balance control was measured as lower-trunk sway angles with body-worn gyroscopes. Expanded Disability Status Scale scores (EDSS) were used to monitor, clinically, disease progression. Results: Remitting-phase patients showed more unstable stance balance control than HCs (p<0.04) with no worsening over the observation period of 9 months. Gait balance control was normal (p>0.06). Relapsing patients had stance balance control significantly worse at onset compared to remitting-phase patients and HCs (p<0.04). Gait tasks showed a significant decrease of gait speed and trunk sway in relapsing patients (p=0.018) compatible with having increased gait instability at normal speeds. Improvement to levels of remitting patients generally took longer than 3 months. Balance and EDSS scores were correlated for remitting but not for relapse patients. Conclusions: Balance in remitting RRMS patients does not change significantly over 9 months and correlated well with EDSS scores. Our results indicate that balance control is a useful measure to assess recovery after a relapse, particularly in patients with unchanged EDSS scores. . Based on our results, balance could be considered as additional measurement to assess recovery after a relapse, particularly in patients with unchanged EDSS. Keywords: Multiple sclerosis; Balance control; Trunk sway; Relapse-phase multiple sclerosis; remitting-phase multiple sclerosis, EDSS scores